RESIKO PEMBIAYAAN MURABAHAH PADA NASABAH MENINGGAL DUNIA DI Bank Aceh Syariah Capem MalikulsalehBank Aceh Syariah Capem Malikulsaleh - Maysarah (FAKULTAS SYARIAH DAN EKONOMI ISLAM IAI ALMUSLIM, 2023)
In financing that is channeled of course there are various kinds of risks that may be faced one of which is financing risk. Financing risk is the risk that occurs due to the failure of members to fulfill their obligations namely in the form of installment payments both the principal of the financing and the margin/financing profit sharing. One of the risks that causes the return of financing is hampered and even becomes jammed, one of which is a disaster such as the death of a customer. In this case the author is interested in researching the Risks of Murabahah Financing on Customers Diing (Case Study of Bank Aceh Shariah Capem Malikulsaleh). To solve the existing problems the author uses a type of field research using a qualitative descriptive approach. The method of data collection that the authors use is the method of interviews, observation, and documentation. In analyzing the data, the researcher summarizes the results of the research by focusing on important things or looking for themes from the research, then the researcher presents the results of his research in the form of a short description that is easy to understand. Research Results Settlements made at the risk of murabahah financing for customers who have died with collateral, this collateral can be in the form of goods or insurance, collateral for objects in the form of collateral in the form of assets if the customer is unable to pay off the debt then the guarantee will be confiscated. The second guarantee is an insurance guarantee that if something unexpected happens such as the death of the customer, the heirs can submit an insurance claim to pay off the customer's debt